Produção e qualidade de alho nobre submetido a diferentes períodos de vernalização e épocas de plantio em Baraúna, RN - Lopes, Welder de Araújo Rangel (Universidade Federal Rural do Semi-Árido, 2014)
In recent years, the use of vernalization enabled the cultivation of noble garlic (most valuable garlic in the Brazilian market) in regions where photoperiod and temperature do not meet the requirements of the crop. Given this, in order to evaluate effects of different vernalization periods and planting dates on the production and quality of the garlic Roxo Pérola de Caçador, an experiment was conducted in Baraúna, RN, between May and October 2012. The experimental design was a randomized complete block design with three replications. The treatments were arranged in splitplots with the plots by planting dates: May 22, June 5 and June 23, and the splitplots by vernalization periods garlic seed at 4 ± 1 °C: 50, 55, 60, 65 and 70 days, and 65-70% of relative humidity. Plant height, leaf number, cycle, bulb final stand, average bulb weight, percentage of bulbs differentiation of cloves, percentage of oversprouting plants, total yield of bulbs, classification of bulbs, number of cloves per bulb, classification of cloves, bulb diameter, soluble solids, total soluble sugars, tritable acidity, pH, SS/AT ratio, pungency, total solids and industrial index were evaluated. The planting on May 22 gave higher plant height, leaf number, final stand and average bulb weight; the cycle decreased with increasing time of vernalization; were formed bulbs with differentiation of cloves in all treatments, and absence of oversprouting of plants; total bulb yield increased with time until 63 days of vernalization during at plantations of May 22 and June 23, with averages of 5.20 and 3.85 t ha-1; by combining the planting on May 22 time and 65 days of vernalization, showed the highest number of cloves per bulb (7.51) and the highest percentage of commercial bulbs, which are distributed in classes 3 (32 to 37 mm diameter), 4 (37 to 42 mm diameter) and 5 (42 to 47 mm diameter). For attributes of quality, the increased length of vernalization up to 64 days allowed in increments bulb diameter and soluble solids, with maximum of 34.5 mm and 33.65%, respectively; the highest levels of total soluble sugars, bulb diameter and soluble solids were obtained at planting on May 22; the tritable acidity increased with time vernalization during plantations of 5 and 23 June, when there was a reduction in SS/AT ratio; and in general, all treatments allowed high total solids and simultaneous pungency, with good prospects for industrialization. Thus, we recommend planting the cultivar Roxo Pérola de Caçador on Baraúna/RN, in the second half of May, using 65 days of vernalization
Production and quality of noble garlic under different vernalization periods and planting dates in Baraúna, RN
Keywords: Allium sativum L.; Cold storage; Yeld; Bulbing level; Soluble solids; Pungency; Allium sativum L.; Frigorificação; Produtividade; Bulbificação; Sólidos solúveis; Pungência; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA